Analysis of Factors Influencing the Resistance of a Type of Air Filter Paper Based on SPSS. (January 2020) - Qi, Peiyun; Yan, Chunxiao; Zang, Chuanqin; Xu, Jiayu; Huang, Xingqi; Dai, Xuezhi; Jin, Yanren; Zhao, Ting
Abstract: The thicknesses, basis weights and resistances of a type of air filter paper randomly sampled were tested by experiment. The statistical analysis of the test data was carried out by multiple linear regression analysis of the statistical software SPSS19.0. The conclusion were as follows: when the paper had a basis weight variation from 55.2 g/m 2 to 59.8g/m 2 and a thickness variation from 0.385mm to 0.406mm, α=0.05, basis weight variation on resistance existed significant influence, the regression equation was Δp=2.551w, correlation coefficient R 2 =0.83; thickness variation on resistance did not exist significant influence.